Prarancangan Pabrik Metil Klorida Dengan Proses Hidroklorinasi Metanol Kapasitas 80.000 Ton/Tahun. - Damaryanti, Ema Suci; , Hamid Abdillah, S.T., M.T (2017)
Methyl chloride is widely used as an intermediate for the production of liquid silicone, elastomers, and certain surfactant compounds such as dimethyl ammonium chloride which is used as fabric softener. In addition, methyl chloride is also used as a heat stabilizer for PVC, cable and wire insulation, adhesives, and tire fabrics. to meet domestic demand and the world. Methyl chloride plant is designed with a capacity of 80,000 tons / year will be operated for 330 days per year and is continuously. The plant will be established in Cilegon, Banten in 2020 The selection of the location is based on supplying of raw materials, labor, transportation, and marketing. Methyl chloride raw materials are methanol and hydrogen chloride with the aid of silica gel alumina catalyst at temperature of 300 - 390.11 oC at 10 atm. The reaction run in a non adiabatic non-isothermal fixed bed reactor, with conversion in the reaction 99% is exothermic, so dowtherm A is required to keep the temperature stable. The phase that occurs is the gas phase. There are some processes the stages of preparation of raw materials, product formation stage, the stage of purification and storage products. The process would need 6,490.5683 kg/hour methanol and 22,347.3389 kg/hour hydrogen chloride. The proposed plant would include the utility unit that need fresh water of 273,421.0116 kg/hour from the closest river, saturated steam of 7,564.2573 kg/hour, compressed air of 13.2523 m3/hour, electrical supply of 1,796.9826 kW from PLN and 2500 kW set of generator as a reserved electricity, and 650.20 liter per hour fuel oil. The company type would be a limited liability company. Economic analysis of the factory shows the percent Return on Investment (ROI) if 45%, Pay Out Time (POT) if 1.8 year, Break Even Point (BEP) if 42.02%, Shut Down Point (SDP) if 20.1% Internal Rate of return (IRR) on the basis of Discounted Cash Flow (DCF) if 21.31%. %. From this analysis, it can be conclude that this plant feasible to set up. Keywords: Methyl chloride, fixed bed reactor, economic analysis.